The provision of NHS health checks in a community setting: an ethnographic account - Riley, Ruth; Coghill, Nikki; Montgomery, Alan; Feder, Gene; Horwood, Jeremy (BIOMED, 2015)
Background: The UK National Health Service Health Checks programme aims to reduce avoidable cardiovascular deaths, disability and health inequalities in England. However, due to the reported lower uptake of screening in specific black and minority ethnic communities who are recognised as being more at risk of cardiovascular disease, there are concerns that NHS Health Checks may increase inequalities in health. This study aimed to examine the feasibility and acceptability of community outreach NHS Health Checks targeted at the Afro-Caribbean community. Methods: This paper reports findings from an ethnographic study including direct observation of four outreach events in four different community venues in inner-city Bristol, England and follow up semi-structured interviews with attendees (n = 16) and staff (n = 4). Interviews and field notes were transcribed, anonymized and analysed thematically using a process of constant comparison. Results: Analysis revealed the value of community assets (community engagement workers, churches, and community centres) to publicise the event and engage community members. People were motivated to attend for preventative reasons, often prompted by familial experience of cardiovascular disease. Attendees valued outreach NHS Health Checks, reinforcing or prompting some to make healthy lifestyle changes. The NHS Health Check provided an opportunity for attendees to raise other health concerns with health staff and to discuss their test results with peers. For some participants, the communication of test results, risk and lifestyle information was confusing and unwelcome. The findings additionally highlight the need to ensure community venues are fit for purpose in terms of assuring confidentiality. Conclusions: Outreach events provide evidence of how local health partnerships (family practice staff and health trainers) and community assets, including informal networks, can enhance the delivery of outreach NHS Health Checks and in promoting the health of targeted communities. To deliver NHS Health Checks effectively, the location and timing of events needs to be carefully considered and staff need to be provided with the appropriate training to ensure patients are supported and enabled to make lifestyle changes.